12: A CONSULTATIONS TRACKING DATABASE SYSTEM FOR IMPROVING FACULTY DEVELOPMENT CONSULTATION SERVICES. (10th October 2017) - Rhode, Jason; Krishnamurthi, Murali
Abstract : The role of the faculty development center in supporting the academic environment of the institution often includes creating or sustaining a culture of teaching excellence, responding to individual faculty members' needs, and advancing new initiatives in teaching and learning (Sorcinelli, Austin, Eddy, & Beach, 2006). The varied programs, resources, and services offered routinely result from efforts to meet the expressed needs of faculty. While workshops and seminars are effective for introducing new pedagogical approaches or emerging technologies, faculty often have unique questions within specialized contexts that cannot be fully addressed in a large group setting. In such instances, a more personalized and customized level of support is needed. This chapter describes a database system for tracking and improving the effectiveness of individual consultation services.